Oracle essentials : Oracle9i, Oracle8i, and Oracle8 - Greenwald, Rick (O'Reilly, 2001)
The second edition of O'Reilly's bestselling Oracle Essentials has been updated to include the latest Oracle release, Oracle9 i. Oracle Essentials distills an enormous amount of information about Oracle's myriad technologies and releases into a compact, easy-to-read volume filled with focused text, illustrations, and helpful hints. Oracle9 i promises to be an even more significant upgrade than Oracle8 i, offering such major features as Real Application Clusters, flashback queries, Oracle personalization, clickstream intelligence, and Oracle Database Cache and Web Cache; it also promises significant improvements in Oracle's business intelligence, XML integration, high availability, and management capabilities. The book includes overviews of these features, as well as the new Oracle9 I Application Server (Oracle9 i AS) and Oracle9 i Portal. The book contains chapters on: Oracle products, options, and overall architecture for Oracle9 i and other recent releases Installing and running Oracle: creating databases, configuring Net8 (known as Oracle Net in Oracle9 i), starting up and shutting down Oracle Oracle data structures, datatypes, and ways of extending datatypes Managing Oracle: security, the Oracle Enterprise Manager, fragmentation and reorganization, and backup and recovery Oracle networking, monitoring, and tuning Multi-user concurrency, online transaction processing (OLTP), and high availability Hardware architectures (e.g., SMP, MPP, NUMA) and their impact on Oracle Data warehousing and distributed databases Oracle9 i, Oracle8 i, and the Web, including the latest Java, web, and XML technologies, interMedia, Oracle9 i Application Server, and Oracle9 i Portal For new Oracle users, DBAs, developers, and managers, Oracle Essentials is an all-in-one introduction to the full range of Oracle features and technologies, including the just-released Oracle9 i features. But even if you already have a library full of Oracle documentation, this compact book is the one you'll turn to, again and again, as your one-stop, truly essential reference.